2011
DOI: 10.1159/000321848
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal-Renal Syndrome: Mirage or Reality?

Abstract: The recent interest in the role of the intestine in the cardiovascular stability of uremic patients, specifically on dialysis, but potentially also in chronic kidney disease, must be seen against the background of the recent great interest in the role of the gut in chronic heart failure [Curr Opin Clin Nutr Metab Care 2008;11:632–639]. There has been a long-standing interest in the role of the intestine in renal failure, mainly concerning the role of metabolites of bacterial metabolism in the gut as potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 172 publications
2
48
0
2
Order By: Relevance
“…Dysfunction of the intestinal barrier in CKD is associated with bacterial translocation and endotoxinemia, which is related to systemic inflammation, malnutrition, cardiovascular disease, and possibly reduced survival [28,72,73,9].…”
Section: Role Of a Disturbed Intestinal Barriermentioning
confidence: 99%
“…Dysfunction of the intestinal barrier in CKD is associated with bacterial translocation and endotoxinemia, which is related to systemic inflammation, malnutrition, cardiovascular disease, and possibly reduced survival [28,72,73,9].…”
Section: Role Of a Disturbed Intestinal Barriermentioning
confidence: 99%
“…The reason of the differences between these results and ours are unclear but they could be related to the different dialysis procedure that was used. Recent evidence suggests, indeed, that the underperfusion that can take place during extracorporeal hemodialysis could alter the permeability of the intestinal barrier favoring the passage of intestinal bacterial products (Intestinal-Renal Syndrome) [34]. Supporting this hypothesis, McIntyre et al recently reported [35] that measurable levels of endotoxins coming from intestinal bacteria can be detected in the plasma of hemodialysis patients and, importantly, that they increase at the time of dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…These important results have been interpreted assuming that dialysis-induced hemodynamic stress could damage the intestinal mucosa finally leading to an increase of its permeability to endotoxins [35]. Although a formal demonstration of this hypothesis by quantitative measurement of intestinal blood flow is still lacking [34], it is tempting to speculate that Sev could be less effective in preventing p-cresol absorption in hemodialysis patients because this dialysis procedure increases the permeability of the intestinal mucosa to the point that too much p-cresol can escape from Sev and enter the blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…U jednom od pionirskih radova, Mallamaci i saradnici su pokazali da je nivo TnT kod bolesnika na hemodijalizi bez akutnog koronarnog sindroma i bez srčane insuficijencije nezavisno povezan sa masom LV i da predviđa ukupni i KV mortalitet [26]. Nakon toga, Wood i saradnici su saopštili da je već blago povišeni nivo TnT kod bolesnika sa HBS pre započinjanja dijaliznog lečenja povezan sa lošim preživljavanjem [27]. U metaanalizi koja je obuhvatila 28 studija, Khan i saradnici su potvrdili da povišeni nivo TnT u grupi asimptomatskih dijaliznih bolesnika identifikuje podgrupu bolesnika sa lošim preživljavanjem i visokim rizikom srčane smrti [13].…”
Section: Uvodunclassified